Community perceptions of Nigerian oil companies commitment to social and environmental concerns. Issue 1 (3rd January 2018) - Odera, Odhiambo; Scott, Albert; Gow, Jeff
Abstract : Purpose: This paper aims to identify factors influencing and shaping community perceptions of oil companies which present fertile ground for a better understanding of their actions. Design/methodology/approach: A qualitative methodology is adopted where primary data were collected through semi-structured interviews from members of three communities in the Niger Delta: Ogbunabali community in Port Harcourt (Rivers State), Biogbolo community in Yenagoa (Bayelsa State) and Ogunu community in Warri (Delta State). The interview data were recorded, transcribed and qualitatively analysed using content analysis with NVivo software. Findings: Perceptions regarding negative and positive aspects of the oil companies were identified. These included environmental concerns; lack of compensation; health effects; lack of social development; neglect of communities; not creating employment opportunities; and providing community and educational support. Research limitations/implications: A major limitation regards the small number of respondents selected from the communities. The sample of the interviewees was constrained by their availability and accessibility, which might have injected some bias. Gathering data from other stakeholders such as non-governmental organisations, consumers, investors and creditors may provide a deeper understanding of social and environmental practices. Another approach would be to extend this study by examining the perceptions of relevant government officials towards social and environmental concerns in developing countries. Originality/value: The qualitative research methodology utilised in this study uses content analysis to examine views of communities about oil companies' commitments to their social and environmental concerns. An understanding of social and environmental commitments allows diverse stakeholders such as communities to become more engaged with issues affecting them.